Conhecimento precário e conhecimento contra-público: a coprodução dos conhecimentos e dos movimentos sociais de pessoas trans no Brasil - Thiago Coacci Rangel Pereira (2018)
The present work sought to analyze the relationship between politics and knowledge in social movements, with a specifc focus on the brazilian Transgender Movement. I depart from a dissatisfaction with how the production of knowledge is treated both on social movements studies and transgender studies. My hypothesis is that knowledge (and science) has become central to contemporary conficts, thus the analysis of social movements today cannot be detached from an analysis of the relations they establish with certain sets of knowledge (scientifc or not). By interacting in the world, building their diagnoses and plans of action, social movements identify precarious knowledge and act by producing or stimulating the production of counterpublic knowledge. The study is anchored empirically in the analysis of the brazilian Transgender Movement. Between 2014 and 2017, I accompanied four organizations: Articulação Nacional de Travestis e Transexuais (ANTRA); Instituto Brasileiro de Transmasculinidade (IBRAT); Rede Trans Brasil; and the Coletivo Transfeminismo. The research was operationalized through the combination of document analysis of minutes, reports, pamphlets; 16 semistructured interviews with activists; and the participant observation of various kind of events, such as academic conferences, social movement meetings, meetings with politicians, etc. The thesis is divided in two major parts. The frst, entitled The Canonical Knowledge, focuses on the production of academic knowledge about trans people and is subdivided into two chapters. The second, entitled The Activist Knowledge, retraces the history of the transgender movement in Brazil and describes two forms of precarious knowledge: the lack of quantitative data on trans people in Brazil; and the poor quality of scientifc knowledge about transgender people, especially in the medical and psy felds. For each type of precariousness identifed by social movement activists, these actors sought strategies to combat it through the production of counter-public knowledge